2019
DOI: 10.1186/s40713-019-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating and validating a combined accumulation and mobilisation model for water distribution system discolouration using particle swarm optimisation

Abstract: A discolouration concept is proposed describing simultaneous pipe wall material accumulation and mobilisation processes that define discolouration in drinking water distribution systems, one of the biggest causes of customer dissatisfaction. Validation of these mathematical forms is presented. The model formulation was shown to maintain the mobilisation functionality of previous validated shear-stress-dependant modelling tool, but requiring only two empirical parameters. Two distinct operational datasets are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Similar conclusions were suggested from previous studies. 35 The accumulation period parameter value of 1.65-1.85 years found here for trunk mains is comparable with that previously for pipes in reticulation or local distribution systems, which found around 1.5 to 2 years in UK systems with cast iron pipes 15 and within 1.5 years in a network in Netherland. 18 Both these studies used calculations from turbidity data to estimate the accumulation period, rather than via model fitting as reported here.…”
Section: Parameters and Accumulationsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar conclusions were suggested from previous studies. 35 The accumulation period parameter value of 1.65-1.85 years found here for trunk mains is comparable with that previously for pipes in reticulation or local distribution systems, which found around 1.5 to 2 years in UK systems with cast iron pipes 15 and within 1.5 years in a network in Netherland. 18 Both these studies used calculations from turbidity data to estimate the accumulation period, rather than via model fitting as reported here.…”
Section: Parameters and Accumulationsupporting
confidence: 90%
“…34 The VCDM simulates discolouration using two validated mobilisation parameters (βe and α; a rate term and a scaling factor respectively), initially tested through synthetic data and then successfully calibrated for small diameter pipes and a single trunk main. 35 The calibration results demonstrated that the VCDM retains the mobilisation functionality of the PODDS model, with comparable quality of fit to measured data. A third parameter is a linear accumulation rate.…”
Section: Modelling Discolouration Processesmentioning
confidence: 74%
See 2 more Smart Citations